One-Stage Hybrid Repair of Multiple Degenerative Aneurysms - George N. Kouvelos; Nektario K. Papa; Eleni M. Arnaoutoglou; Christina Bali; Miltiadis I. Matsagkas (Case Reports in Vascular Medicine)
The development of multiple aneurysms in different segments of the arterial tree requiring treatment is a challenge for the vascular surgeon as their management often demands more than one surgical procedure. We report a case of a 71-year-old male suffering from multiple aneurysms in four different segments of the arterial tree in combination with disabling claudication of his left leg. The patient was managed in a single session with a combination of classic open surgical and endovascular techniques in order to treat his aneurysms and revascularize his leg. This case illustrates the prospect to combine classic open surgical and endovascular techniques for the optimal management of multileveled arterial pathology. Combined therapy simplifies management and allows the one-stage treatment of these patients, while minimizing the overall operative risk.